The Role of the Employee Work Motivation in Mediating the Work Culture towards Their Performance - Ida Ayu Oka Martini; I Wayan Gde Sarmawa (Jurnal Ekonomi & Bisnis JAGADITHA, 2019)
The rapid development of the hospitality business in Bali has led to increasingly fierce competition among hoteliers. This encourages every hotel business competing to provide the best facilities and services to maintain the continuity of its business. However, this is highly dependent on the good and bad performance of the service of the employees towards hotel consumers. Employee performance is influenced by a number of factors, including the work culture and work motivation of each employee. This research aims to determine the effect of work culture and employee motivation on the performance of non-star hotel employees in Denpasar-Bali. This research was supported by 100 randomly selected employees at 25 non-star hotels in Denpasar-Bali. Data collection is done by conducting direct interviews with prepared questionnaire guidelines. Furthermore, for the data collected, the analysis is carried out using the SmartPLS 3.0 program. The results of data analysis show that work culture has a significantly positive effect on the employee work motivation, and likewise the work motivation has a significantly positive effect on the employee performance. On the other hand, the work culture shows a more significantly positive influence on the employee performance. Based on this, it can be said that the work motivation has a role as mediating the relationship between the work culture and the employee performance partially.